Cover Feature: Synthesis, Photophysical and Electronic Properties of New Red‐to‐NIR Emitting Donor–Acceptor Pyrene Derivatives (Chem. Eur. J. 2/2020). Issue 2 (21st November 2019) - Merz, Julia; Dietz, Maximilian; Vonhausen, Yvonne; Wöber, Frederik; Friedrich, Alexandra; Sieh, Daniel; Krummenacher, Ivo; Braunschweig, Holger; Moos, Michael; Holzapfel, Marco; Lambert, Christoph; Marder, Todd B.
Abstract : The synthesis of three new pyrene derivatives with strong donors at the 2, 7‐positions and acceptors at the K‐region is depicted in the cover artwork, designed by Jan Maier. This leads to unusual properties such as emission in the red to NIR region (700 nm), long intrinsic lifetimes of >100 ns and the monocations absorb up to 3000 nm. More information can be found in the Full Paper by T. B. Marder et al. on page 438 .